2020
DOI: 10.1080/10899995.2020.1779567
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate learning in the field: Designing experiences, assessing outcomes, and exploring future opportunities

Abstract: Dear (First name),As part of an NSF-funded Research Coordination Networks grant, the Undergraduate-Field Experiences Research Network (UFERN) seeks to foster effective undergraduate field experiences. As the network gets started, we could use your help characterizing the nature of undergraduate field programs offered at your institution. We ask that you please use the link below to complete our survey, which should take approximately 20 minutes to complete.Please follow this link to take the survey: Take the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…Research in this area has tended to focus on understanding the challenges of students’ initial field experiences and supporting students. As noted by O’Connell et al (2020), there is both an empirical and a pedagogical need for well-designed tools to evaluate the impact of field-based learning on students.The challenge of working and learning in a place one has never been in before has been captured by the concept of novelty space , which is the notion that when students are in a new space, there are cognitive, geographic, and psychological barriers to overcome before learning can occur. Orion and Hofstein (1994) found that when students’ novelty spaces were minimized (e.g., through awareness of what to expect in a new area and recognition of the social-emotional effects of being in new places), learning was optimized.…”
Section: Opportunities and Challenges Of The Specific Stem Disciplinesmentioning
confidence: 99%
“…Research in this area has tended to focus on understanding the challenges of students’ initial field experiences and supporting students. As noted by O’Connell et al (2020), there is both an empirical and a pedagogical need for well-designed tools to evaluate the impact of field-based learning on students.The challenge of working and learning in a place one has never been in before has been captured by the concept of novelty space , which is the notion that when students are in a new space, there are cognitive, geographic, and psychological barriers to overcome before learning can occur. Orion and Hofstein (1994) found that when students’ novelty spaces were minimized (e.g., through awareness of what to expect in a new area and recognition of the social-emotional effects of being in new places), learning was optimized.…”
Section: Opportunities and Challenges Of The Specific Stem Disciplinesmentioning
confidence: 99%
“…A scan of the literature yielded limited direct quantitative evidence specifically connecting undergraduate field experiences in ecology to preparing students for the workforce (O’Connell et al 2020). Most of the literature discussed in this paper was related to the geosciences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many field‐related majors offer internships and laboratory courses to better prepare students for their chosen career path. There is also a general agreement that fieldwork provides skills and knowledge that cannot be learned in a classroom setting (Aplet et al 2017, Fleischner et al 2017, Byers 2018, O’Connell et al 2020, Morales et al 2020). However, while field programs at the undergraduate level have been offered for decades, they are often not required for graduation in a field‐related major.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations